Word of Mouth (WOM) as Marketing Strategy Towards Ship Sales at PT. Multi Daya Unggul - Ervin Muhammad Dermawan; Cecep Safa'atul Barkah (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2023)
PT. Multidaya Unggul wants to achieve its goal of being able to create a worldwide market through a marketing strategy. With this aim, the marketing strategy used is word of mouth. In this study, the method used is qualitative descriptive analysis. The research was conducted by observing, in-depth interviews, and studying documentation at the company. From the data obtained through the research stages, then an analysis was carried out using elements from word of mouth, it is known that PT. Multidaya Unggul chooses its loyal customers to promote its products to potential customers, especially those in the middle to upper economic class. The existence of a word of mouth is due to the creation of a message or event that makes them talk about the product or service they have used.